2021
DOI: 10.15251/jor.2021.175.461
|View full text |Cite
|
Sign up to set email alerts
|

Half metallic ferromagnetism and optoelectronic characteristics of V doped BaTiO3compound: a DFT study

Abstract: The effect of vanadium (V) doping with various concentrations (x= 12.50%, 25%, 50%, 75%) on the physical properties ofBaTiO3perovskite is examined using the spin polarized theory.The electronic band structure (BS) for both states reveal that all Ba0.875V0.125TiO3, Ba0.75V0.25TiO3,Ba0.5V0.5TiO3 and Ba0.25V0.75TiO3 compounds are half-metallic ferromagnetic (HMF) materials. The results showed that V play a significant role in the HMF behavior ofBa1-xVxTiO3compound. In addition, the magnetic characteristics confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Based upon presented analysis, V-doped LAO shows a similar-like trend as reported in previous studies. [40][41][42]…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Based upon presented analysis, V-doped LAO shows a similar-like trend as reported in previous studies. [40][41][42]…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Doping is one of the most powerful tools for improving the physical properties of FE PO. As Sohail et al, theoretically explained the 3d transition metal (TM) doping effect on the BTO system, where TM is substituted at A-site and found that V-doped motif exhibits HM FM behavior [35]. A MF motif was synthesized experimentally at room temperature by Palker et al, [36] by doping Fe at the Ti site in PTO structure.…”
Section: Introductionmentioning
confidence: 99%
“…Spintronic investigations were first limited to metals, but recently, several semiconducting materials have been recognized as FM materials, making them important for applications in practical devices. [ 1,2 ] A material's suitability for spintronic applications depends on its room‐temperature FM nature. [ 3 ] The ionic distribution in spinel chalcogenides is believed to be responsible for the strong exchange splitting between cation and anion states.…”
Section: Introductionmentioning
confidence: 99%